ISLAM DAN SOSIAL POLITIK DEKADE 1990 –AN (Sebuah Wacana Politik Islam Pasca Orde Baru) - Ainur Ropik (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
Political Islam from the beginning independence of Indonesia, 1950 's ( old order ) until the mid- 1983 era New Order have a situation that according to Islam is very harmful , because Muslims feel marginalized in addition to the majority of Indonesia's population is Muslim Islamic politics it can not grow because of the emphasis that is made by new order all Islamic political movements and activities are supervised and in the limit . After doing some of the terms in the proposed new order government to Islamist parties at the time that the fusion of Islamic political parties Political Islam at the end of late New Order era began to rise and begin accommodated . With accommodation of political Islam into the governance of the New Order era many beneficial changes to the entry of Political Islam Islamic leaders into the government bureaucracy in both the legislative , judicial and other reforms to transform the era of the New Order era and replace . This paper will try to outline the state of the back of political Islam in the era of the New Order and post-New Order political Islam .